CULTURAL CONTENT ANALYSIS ON GOVERNMENT-ISSUED ENGLISH LEARNING TEXTBOOKS - Ryan Ghassan Albari; Harumi Manik Ayu Yamin (Universitas Islam Nahdlatul Ulama Jepara, 2020)
In today’s world, the English language is seen as the international language for its world-wide use in all aspects of life. The language thus becomes the medium in bridging communication gaps between countries by providing a common ground for communication. To cater to the need of human resources with intercultural communicative competence (ICC), the government in Indonesia has issued textbooks for English learning for middle school students. In Indonesian national curriculum, English language is first formally learned in middle school, where the students are at the age of shaping their own ideology and values, which could also come from learning. This study examines the English textbooks issued by the government by analyzing their cultural content. The cultural elements are examined and divided into three components using the framework from Yuen’s cultural elements, a modified version of Cortazzi and Jin’s cultural aspects by Tazeddin & Teimournezhad, and Gomez Rodriguez’s surface culture and deep culture. The results show that the cultural content is disproportionate, and it might lead to the failure of creating ICC learners as it dismisses other aspects and elements of culture that are important in nurturing ICC.